2012
DOI: 10.1108/02652321211210886
|View full text |Cite
|
Sign up to set email alerts
|

Customer intention to adopt a fee‐based advisory model

Abstract: Purpose-The paper aims to identify which factors determine (German) retail banking customers' intention to adopt a new remuneration system for financial advice. The new system is a pay-per-use advisory model that supersedes existing commission-based advisory approaches. Design/methodology/approach-The paper develops and tests a comprehensive conceptual framework that includes perceived innovation characteristics, relationship quality, and socio-demographic and psychographic variables to explain adoption intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Dimitriadis et al (2011) have shown that trust factors are also a major segmenting consideration when customers consider alternative banking channels (internet vs phone banking). The application of psychographics has been applied in numerous recent studies of the lender-borrower relationship including Machauer and Morgner (2001) who use the segmentation approach to cluster around specific needs of bank customers; Kaynak and Harcar (2005) who use attitudinal approaches to show preferences by bank customers for local banks vs national banks; Milner and Rosenstreich (2013) who use psychographics to investigate use of financial services by baby-boomers; Foscht et al (2010) who use demographics and psychographics to investigate drivers of satisfaction for credit vs debit card use; and Hoffmann et al (2012)…”
Section: Ijbm 322mentioning
confidence: 99%
“…Dimitriadis et al (2011) have shown that trust factors are also a major segmenting consideration when customers consider alternative banking channels (internet vs phone banking). The application of psychographics has been applied in numerous recent studies of the lender-borrower relationship including Machauer and Morgner (2001) who use the segmentation approach to cluster around specific needs of bank customers; Kaynak and Harcar (2005) who use attitudinal approaches to show preferences by bank customers for local banks vs national banks; Milner and Rosenstreich (2013) who use psychographics to investigate use of financial services by baby-boomers; Foscht et al (2010) who use demographics and psychographics to investigate drivers of satisfaction for credit vs debit card use; and Hoffmann et al (2012)…”
Section: Ijbm 322mentioning
confidence: 99%
“…Of course, there might be reasons other than portfolio diversification that explain why advised customers obtain lower returns. The impact of advisors on customers’ investments has also been discussed from the perspective of price models (Hoffmann et al , 2012). As mentioned in “Introduction”, the practice of financial advisory services also implies a meeting between a buyer and a seller.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The service is marketed as “advice”, and the seller is called an “advisor”[2]. Hoffmann et al (2012) explored consumer willingness to adapt to a new remuneration system that is fee based instead of the commission‐based system used in Germany. They found no evidence that relational factors directly impact adaptation intentions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Seven studies examined the effect of adoption and use of various forms of smart cards such as credit cards and debit cards (e.g. Plouffe et al , 2000; Worthington et al , 2007), new payment technologies such as debit and credit cards, fee-based advisory systems (Hoffmann et al , 2012), mobile payment systems (Arvidsson, 2014), and Islamic home financing (Amin et al , 2013). From the remaining studies ( n =61), four studies examined adoption of ATMs and the other 57 studies focussed on various forms of banking – phone, electronic, internet, or mobile banking.…”
Section: Analysis and Resultsmentioning
confidence: 99%